Patient Engagement in Evidence-Based Practice Frameworks - Jarrod Dusin PhD, RD, CPHQ; Jill Peltzer PhD, RN (Journal of Patient Experience, 2024)
Evidence-based practice (EBP) is the cornerstone of contemporary healthcare, promoting the integration of scientific evidence, clinical expertise, and patient values to inform clinical decision-making and enhance patient outcomes. While patient engagement is recognized as a critical component of EBP, the extent to which it is incorporated in various EBP frameworks is unclear. This study is a secondary analysis of a scoping review which evaluated EBP frameworks used in healthcare settings. In the current study, our objective was to assess the level of patient engagement within those frameworks. To achieve this, we employed a patient engagement framework which characterizes engagement as a continuum, spanning consultation to involvement to shared leadership/partnership, across 3 healthcare domains: direct care, organizational design and governance, and policymaking. Our analysis revealed a gap in integrating patient values and preferences within EBP frameworks. Only 3 of the assessed frameworks showed a high degree of engagement across all domains. Future research should focus on developing strategies for implementing and evaluating meaningful engagement in EBP.